Against All Odds: Migrant and Seasonal Agricultural Workers Seek to Improve Their Lives Through the GED and it’s Impact on Parent Involvement - Maria Mejorado; Raquel Gonzales (Adult Education Research Conference, 2010)
Our presentation will focus upon a group of seasonal agricultural workers, enrolled in GED classes. To what extent are Latino parents currently involved in the schooling of their children? Does studying for the GED impact the depth and scope of their involvement? What implications does this have for increasing parent involvement in schools? In particular, how can more fathers become engaged in schools?